Feasibility and acceptability of the Trans-theoretical Model-based advance care planning for community-dwelling older adults with chronic diseases in China: a randomized controlled trial - Feng, Siyuan; Chen, Jufeng; Zhao, Mingli; Zhuo, Yijia; Zhao, Xinyue; Wang, Xue; Qiao, Beibei (Frontiers in Public Health, 2025)
BackgroundAdvance care planning (ACP) has emerged as a structured process to honor participants’ autonomy in medical decision-making. Evidence indicates that participation in ACP among community-dwelling older adults with chronic conditions is associated with enhanced medical autonomy, improved quality of life, and reduced decisional burden for family caregivers. However, given cultural nuances specific to China, ACP implementation remains limited and underinvestigated, underscoring the necessity of feasibility studies to guide subsequent research and practice.DesignA 6-week feasibility randomized controlled trial was conducted in community settings, with 44 older adults enrolled in Zhengzhou, China. Methods: A randomized controlled design was employed. A total of 44 community-dwelling older adults with chronic diseases meeting the inclusion criteria were recruited and randomly assigned to either the intervention group (n = 22) or the control group (n = 22). The intervention, delivered between August and September 2024, consisted of a Trans-theoretical Model (TTM)-guided program designed to enhance ACP participation. Data were collected at four time points: baseline (T0), immediately post-intervention (T1), 1-month follow-up (T2), and 3-month follow-up (T3) with validated questionnaires used to assess ACP knowledge, attitudes, and participation. Statistical analyses were performed using SPSS 26.0, with primary outcomes including scores for ACP knowledge, attitudes, and participation to evaluate intervention efficacy.ResultsOf the 44 enrolled participants, 4 were lost to follow-up, resulting in an attrition rate of 9.1% and a final sample size of 40. At baseline, all participants were in the precontemplation stage of ACP engagement. Immediately post-intervention, behavioral changes toward ACP participation were demonstrated by 17 participants (85%) in the intervention group. The intervention group exhibited significantly higher scores in ACP knowledge, attitudes, and participation at T1, T2, and T3 (all p < 0.001). For participation scores, significant effects were observed for group (Wald χ2 = 25.965, p < 0.001), time (Wald χ2 = 454.226, p < 0.001), and group time interaction (Wald χ2 = 504.720, p < 0.001).ConclusionThe TTM-based ACP intervention shows promise in potentially improving ACP knowledge, attitudes, self-efficacy, and readiness among community-dwelling older adults with chronic diseases in this feasibility trial. Further research is warranted to highlight the need for larger-scale, multi-center trials with follow-up to further validate the intervention’s efficacy.